Study the Relation of dye laser pulses with its concentration for the Rhodamine B dye - Hadi, Naseer Mahdi; Jassim M. Najim; Mohammed , Noor Adnan (International Journal of Psychosocial Rehabilitation, 2020)
The work includes the study of some optical and physical properties of rhodamine B dye in ethanol solvent at different concentrations (1x10-5 , 2x10-5 , 4x10-5 , 1x10-4 , 5x10-4, 1x10-3, 5x10-3 mol/L) at room temperature, study and calculation the density and energy of the productedlaser . The UV absorption spectra and fluorescent emission intensity of Rhodamine B (Rh B) dye were determined at different concentrations. The results showed that the intensity and wavelength of the peak of the absorption spectrum for rhodamine B depends on increasing the concentration of the dye leading to increased interference between the absorption spectrum and fluorescence. It was found that in the case of rhodamine B dye, the laser intensity decreased, if the concentration of rhodamine B increased.DYE output energy, full-width-at-half-maximum (F.W.H.M) , intensity and efficiency was calculated for different concentration of RB at maximum wavelength and we got the following at the highestconcentration:(15.5mJ,8.57nm,9793.27counts,44.03%) respectively where the maximum energy was included (35.2mJ).